A Netnographic Study on TikTok: Exploring Anti-Corruption and Audit Themes in Prabowo's Presidential Speech - Pasolo, Muhammad Ridhwansyah; Pasolo, Fahrudin (The Eastasouth Journal of Social Science and Humanities, 2025)
This study employs a netnographic approach to analyze public reactions on TikTok to President Prabowo Subianto's anti-corruption speech, focusing on the themes of audit and governance. A total of 129,000 comments were collected, with 24,193 comments (19%) deemed relevant, while 105,777 comments (81%) were classified as non-relevant. The thematic analysis revealed that the largest proportion of relevant comments (46.26%) expressed positive support for the president, with significant attention given to issues of corruption (6.55%), hope for change (6.57%), and calls for a clean government (6.15%). Although the audit theme appeared in only 1.4% of comments, it revealed a modest but meaningful interest in auditing processes within local governance. Other notable themes included village heads and the inspection of public funds. The study also highlighted a prevalence of non-relevant comments, often driven by netizens seeking engagement with the TikTok admin, reflecting a broader trend of performative interaction. Despite this, the research shows that TikTok remains an effective platform for fostering public discourse on political issues and governance. The findings suggest that social media, particularly platforms like TikTok, can play a crucial role in shaping public opinion on anti-corruption policies and can be strategically used to engage citizens in discussions about transparency and accountability.